Study on Patent Strategy of Emerging industry in China - Bao Meng-meng; Wu Jian-long (E3S Web of Conferences, 2021)
Patent strategy has become an important strategic means to elevate independent innovation capability and international competitiveness of emerging industry. Thus, based on connotation analysis of patent strategy of emerging industry, the paper designs influencing factors analysis framework for industry patent strategy, and puts forward industry patent strategy position, and then builds promoting process of industry patent strategy around patent development, application, use and protection, so as to provide theory and method support for patent strategy management of emerging industry.